(untitled) - Hansen, Andrew J (New York, 1992)
This volume examines the effect of ecotone patterning on comminity diversity and landscape functioning. Ecotones (transition zones between ecosystems) define ecosystem boundaries and may control the flow of energy, material and organisms between ecosystems. This book explores the role of ecotones in controlling these flow thereby influencing landscape functioning. It synthesizes existing theory, evaluates central hypotheses relative to empirical and simulation data, and puts forth new hypotheses
Keywords: biological diversity,ecotones,lanscape ecology,vegetation boundaries